The natural rubber industry : its development, technology, and economy in Malaysia - Barlow, Colin (Kuala Lumpur : New York : Oxford University Press, 1978)
This book records and analyzes the development of the Peninsular Malaysia rubber industry. It explores the process in its historical, technological, social, political, and economic aspects, with major emphasis on the latter. It also examines some international issues in the development of natural rubber, especially as they relate to Malaysia.
Includes index.
Includes bibliographical references: p. 460-486.
ne 21/01/2019
Loans
Keywords: Rubber industry and trade; Rubber; Malaysia